595 Penetrating Pelvic Trauma from a Crossbow Bolt: An Unusual Choice of Weapon. (12th October 2021) - Ting, A; Barnetson, C; Joegi, A; Gibbs, R
Abstract: Introduction: The crossbow was a popular weapon in medieval times due to their relative ease of use and accuracy but was superseded by firearms around the 16th century. Today, it is legal for adults in the UK to own a crossbow without a licence. Case Report: A young adult male victim was brought to a Major Trauma Centre with a single lower left quadrant penetrating wound caused a crossbow bolt that was self-removed immediately after the injury. A 2.5cm entry wound was present with no exit wound. The patient was haemodynamically unstable on arrival and was transferred to theatre without imaging within 16 minutes of arrival. The main operative findings were multiple small bowel serosal tears, a full thickness small bowel injury with no contamination and a left external iliac artery injury with active bleeding which were all repaired primarily. The post-operative recovery course included occlusive left cephalic and antecubital vein thrombi and an extensive non-occlusive left common femoral vein thrombus treated with anticoagulant therapy but was otherwise unremarkable. He was discharged 10 days later with no lasting sequelae at 6-week follow up. Discussion: This case highlights a rare but important and likely underreported modality of penetrating injury. Crossbow bolts have low kinetic energy compared to bullets but high penetrative force, thus little energy is transferred to surrounding tissues. Hence the main injuries caused by crossbow bolts are due to direct damage to structures they come into contact with. Although rare, trauma surgeons should be aware of the pattern of injury caused by crossbows.